(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The purpose of this article is to improve cooperation between district institutions and preschool education organizations based on modern requirements, transform the management system, and improve the quality of education. The study analyzes existing problems, their socio-pedagogical causes, and solutions.